Metabolic and clinical effect of alpha-lipoic acid administration in schizophrenic subjects stabilized with atypical antipsychotics: A 12-week, open-label, uncontrolled study - Fiammetta Iannuzzo; Gianpaolo Antonio Basile; Domenica Campolo; Giovanni Genovese; Gianluca Pandolfo; Loretta Giunta; Domenica Ruggeri; Antonino Di Benedetto; Antonio Bruno (Elsevier, 2022)
Background: Many of the atypical antipsychotics induce metabolic side effects, limiting their use in clinical practice. Alpha-lipoic acid (ALA) was proposed as a new approach in schizophrenia to improve metabolic effects of atypical antipsychotics. The aim of the study is to evaluate the effect of ALA on metabolic and clinical parameters among schizophrenic subjects. Methods: 15 schizophrenic subjects, in stable atypical antipsychotic monotherapy were included in the study. ALA was administrated at the oral daily dose of 600 ​mg/d in addition to antipsychotic therapy. Metabolic, clinical, and psychopathological parameters were measured at typical antipsychotics. e initial screening, and after 12 weeks. Results: ALA produced a statistically significant reduction in QTc (p ​= ​0.012), blood glucose (p ​= 0.005), AST (p ​= ​0.021), γGT (p ​= ​0.035), CPK (p ​= ​0.005) and prolactinaemia (p ​= ​0.026). In contrast, there was a significant increase in HbA1c (p ​= ​0.026). No effects on body weight and blood lipid levels (triglycerides, total cholesterol, HDL, LDL) emerged. Conclusions: ALA treatment appeared to be effective for reducing diabetes risk, liver functionality parameters, hyperprolactinaemia and QTC interval. ALA appears to be safe as adjunctive components in schizophrenia.